EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN ANAK DEMAM TIFOID DI RUMAH SAKIT BHAYANGKARA BANDAR LAMPUNG - Nabila Amanda Putri Rusmiyanto; Gusti Ayu Rai Saputri; Nofita Nofita (Jurnal Ilmiah Wahana Pendidikan, 2026)
Typhoid fever is an acute systematic infectious disease affecting the reticuloedothelial system, gastrointestinal lymph nodes, and gall bladder caused by Salmonella typhi bacteria. Typhoid fever is the number one most common disease in Bhayangkara Hospital. Treatment of typhoid fever using antibiotics. The antibiotics used are very important to pay attention to their use. The purpose of this study was to determine the evaluation of antibiotic use in children with typhoid fever at Bhayangkara Bandar Lampung Hospital based on the 2011 Permenkes, namely the right indication, the right diagnosis, the right drug, the right patient, the right dose, the right way of administration, the right time interval for administration, the right duration of administration, alert side effects. The method used in this study is retrospective which is non-experimental (observational). Data were taken from patient medical records in March 2024 and samples obtained were 52 pediatric typhoid fever patients, with the use of Cefalosporin generation III antibiotics, namely Ceftriaxone as many as 42 patients (80.8%), Cefotaxime as many as 6 patients (11.5%), Thiamfenikol as many as 3 patients (5.8%). Evaluation of the use of typhoid fever drugs that meet the right indication category, the right diagnosis, the right drug, the right length of hospitalization and side effects alert has 100% accuracy, while in the right patient it is 98.08%, the right dose is 94.24% and the right method of administration is 98.08%.